Relative longevity of Leptosphaeria maculans and associated mycobiota on canola debris - Baird, R.E.; Philips, D.V.; Mullinix, B.G.; Alt, P.J. (Phytoprotection, 1999)
Survival of the blackleg pathogen (Leptosphaeria maculans) in canola (Brassica napus var. oleifera) stem debris was studied at three locations during two separate tests from August 1995 through October 1998. In combined isolation frequencies from both locations, L maculans decreased over time from 85.0% before burial in July to 15.4% in September and 3.4 % in December. Eleven months after initiation of this test, L maculans could not be isolated from the infected canola stem pieces. Isolation frequencies of L maculans were similiar among the three soil depths over all sampling dates at both locations. AH other fungi that were present in a preliminary assay also declined after burial. Trichoderma spp. were undetectable after initiation of the test and increased to 27.5 % on the last sampling date in July 1996. The increase of Trichoderma spp. corresponded with the decrease in isolation frequencies of L maculans and other fungi in the stem pieces. The first test differed from previous studies, consequently a second test located near Griffin, Georgia, was initiated in 1996. In the second test, the relative longevity of L. maculans was determined on intact debris (two to three times greater in size) left on the soil surface after harvest in a field using either minimum or no-tillage. Leptosphaeria maculanswas isolated from 26.4,31.2, and 20.8 % of the pieces, respectively, for May 1997, November 1997, and October 1998. Pycnidia containing viable conidia were also identified on 43.7, 26.4, and 18.0% from debris present in the D-V-8 plates even though no visible fungal colonies of L. maculans grew on the agar. The difference in relative longevity of L. maculans between the two tests was directly related to the condition and size of the canola debris. In the first test, the debris was sectioned into 10-cm pieces. These pieces were badly deteriorated and fragmented 5 months after burial. In contrast, the debris in the second test was still intact 36 months after being placed on the soil surface. This survival was because of increased debris size that resulted in reduced fragmentation from tillage. Thus, intact canola debris can serve as an inoculum source for at least three seasons or longer.